Maximizing kidneys for transplantation using machine perfusion: from the past to the future. Issue 40 (October 2016) - Hameed, Ahmer M.; Pleass, Henry C.; Wong, Germaine; Hawthorne, Wayne J.
Abstract: Background: The two main options for renal allograft preservation are static cold storage (CS) and machine perfusion (MP). There has been considerably increased interest in MP preservation of kidneys, however conflicting evidence regarding its efficacy and associated costs have impacted its scale of clinical uptake. Additionally, there is no clear consensus regarding oxygenation, and hypo- or normothermia, in conjunction with MP, and its mechanisms of action are also debated. The primary aims of this article were to elucidate the benefits of MP preservation with and without oxygenation, and/or under normothermic conditions, when compared with CS prior to deceased donor kidney transplantation. Methods: Clinical (observational studies and prospective trials) and animal (experimental) articles exploring the use of renal MP were assessed (EMBASE, Medline, and Cochrane databases). Meta-analyses were conducted for the comparisons between hypothermic MP (hypothermic machine perfusion [HMP]) and CS (human studies) and normothermic MP (warm (normothermic) perfusion [WP]) compared with CS or HMP (animal studies). The primary outcome was allograft function. Secondary outcomes included graft and patient survival, acute rejection and parameters of tubular, glomerular and endothelial function. Subgroup analyses were conducted in expanded criteria (ECD) and donation after circulatory (DCD) death donors. Results: A total of 101 studies (63 human and 38 animal) were included. There was a lower rate of delayed graft function in recipients with HMP donor grafts compared with CS kidneys (RR 0.77; 95% CI 0.69–0.87). Primary nonfunction (PNF) was reduced in ECD kidneys preserved by HMP (RR 0.28; 95% CI 0.09–0.89). Renal function in animal studies was significantly better in WP kidneys compared with both HMP (standardized mean difference [SMD] of peak creatinine 1.66; 95% CI 3.19 to 0.14) and CS (SMD of peak creatinine 1.72; 95% CI 3.09 to 0.34). MP improves renal preservation through the better maintenance of tubular, glomerular, and endothelial function and integrity. Conclusions: HMP improves short-term outcomes after renal transplantation, with a less clear effect in the longer-term. There is considerable room for modification of the process to assess whether superior outcomes can be achieved through oxygenation, perfusion fluid manipulation, and alteration of perfusion temperature. In particular, correlative experimental (animal) data provides strong support for more clinical trials investigating normothermic MP. Abstract : Supplemental Digital Content is available in the text